Effects of Lead and Arsenic in Soils from Former Orchards on Growth of Three Plant Species. (26th April 2022) - Fritz, Bradley G.; Appriou, Delphine; Counts, Jonathan R.; Sample, Bradley E.; Bunn, Amoret L.; Dimson, Jared F.; West, Molly T.
Abstract: Historical use of lead arsenate as a pesticide in former orchards of eastern Washington State (USA) has resulted in legacy lead (Pb) and arsenic (As) soil contamination. However, the impacts on plant growth in soils with residual Pb and As contamination have not yet been quantified. To this end, a comparative study of plant growth impacts was performed for native bluegrass ( Poa secunda ), invasive cheatgrass ( Bromus tectorum ), and buttercrunch lettuce ( Lactuca sativa ). Using standard plant growth protocols, germination frequency and biomass growth were measured over a wide range of Pb and arsenate concentrations, with maximum concentrations of 3400 and 790 mg kg −1 for Pb and As, respectively. Results indicated that only the biomass growth for all species decreased in soils with the highest concentrations of Pb and As in the soil, with no impacts on soils with lower residual Pb and arsenate concentrations. No impact on percentage of germination was observed at any soil concentration. These results can be used to determine site‐specific soil screening levels for use in ecological risk assessments for Pb and arsenate in soils. Environ Toxicol Chem 2022;41:1459–1465. © 2022 Battelle Memorial Institute. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.